2020
DOI: 10.1021/acs.energyfuels.9b03577
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Structure Modifiers as a Novel Approach for Viscosity Reduction in Heavy Crude Oils

Abstract: Heavy crude oils constitute the largest reserves; however, their extraction faces several challenges as a result of their high asphaltene content. Reducing the viscosity by physicochemical treatments or chemical transformation on heavy asphaltenes is still a challenge because of matrix complexity. On the other hand, the 1,3-dipolar cycloaddition (1,3-DC) reaction has been used to increase the solubility and rheological properties of graphene and fullerenes, suggesting that 1,3-DC on heavy crude oils can modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In one of the mechanisms, additives interact with the polar groups of asphaltenes and resin molecules by breaking the original hydrogen bonding, leading to viscosity reduction. 83 In other mechanisms, chemical additives inhibit reaggregation of asphaltenes and resin molecules and attributes to the reduction in viscosity of bitumen. 84 The workability of an asphalt mixture is primarily affected by the interaction between the binder and fine aggregate particles.…”
Section: Cavitation-assisted Viscosity Reduction Of Bitumenmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the mechanisms, additives interact with the polar groups of asphaltenes and resin molecules by breaking the original hydrogen bonding, leading to viscosity reduction. 83 In other mechanisms, chemical additives inhibit reaggregation of asphaltenes and resin molecules and attributes to the reduction in viscosity of bitumen. 84 The workability of an asphalt mixture is primarily affected by the interaction between the binder and fine aggregate particles.…”
Section: Cavitation-assisted Viscosity Reduction Of Bitumenmentioning
confidence: 99%
“…In these approaches, the mechanism of viscosity reduction depends on the interaction of additives with asphaltenes and resin molecules. In one of the mechanisms, additives interact with the polar groups of asphaltenes and resin molecules by breaking the original hydrogen bonding, leading to viscosity reduction . In other mechanisms, chemical additives inhibit reaggregation of asphaltenes and resin molecules and attributes to the reduction in viscosity of bitumen …”
Section: Cavitationally Driven Transformations In Bitumen Processingmentioning
confidence: 99%
“…Heavy oils have a considerable amount of asphaltene-resinous components, heteroatoms (S, N, and O), and metals (vanadium and nickel) . The asphaltenes in heavy oils contain iron, vanadium, and nickel (up to 1%), of which the proportion of vanadium is more than 80%. , Vanadylporphyrins, one of the most common forms of crude oil metalloporphyrins, play an important role in asphaltene aggregation, fouling, and deposition. …”
Section: Asphaltene Structurementioning
confidence: 99%
“…A study showed that pyrene entered porous asphaltene nanoaggregates to form host–guest complexes through significant interaction between asphaltene aggregates and pyrene molecules . Although many attempts have been made through designing aromatic VRAs based on the asphaltene interaction by π–π stacking, hydrogen bonds, etc., , to the best of our knowledge, pyrene has never been used for viscosity reduction of heavy oil. The synthesized copolymer PAP contains 3.7 mol % of pyrene units, which leads to phase separation of the polymer in high-salinity brine.…”
Section: Introductionmentioning
confidence: 99%